![\frac{x}{3} - \frac{y}{6} = \frac{5}{6} \frac{x}{3} - \frac{y}{6} = \frac{5}{6}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B3%7D+-+%5Cfrac%7By%7D%7B6%7D+%3D+%5Cfrac%7B5%7D%7B6%7D)
3x - 2y = 9
Solve Simultaneous Equation
Answers
Answered by
1
Answer
x = 1 and y = -3
Explanation
Given,
-
=
=> *
-
=
=> -
=
=> 2x-y = 5 -------------- (1)
and 3x-2y = 9 --------------- (2)
(1)*2 - (2) =>
4x - 2y - (3x - 2y) = 10-9
=> 4x-3x -2y + 2y = 1
=> x = 1
substitute x=1 in (2)
3(1) - 2y = 9
3-2y = 9
2y = 3-9
2y = -6
y = -6/2
y = -3
Answered by
2
On solving by elimination method :
____________________________
On subtracting :
On putting the value of y in equation (1) :
So, the values of x and y are 1 and -3 respectively.
Similar questions